MENGUJI KAUSALITAS ANTARVARIABEL EKONOMI DAN POLITIK: IBN KHALDUN THEORY ON WEALTH - Rusydiana, Aam Slamet (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2018)
One of the Muslim scholars called the historian of Schumpeters world is Ibn Khaldun. This figure has realized the great impact of economic factors on social and political life. Ibn Khalduns formulation shows the composite and relationship of variables that are the prerequisites for the realization of a state (G). The variables are syariah (S), society (N), wealth (W), and development (D). This research will try to test the relation between several economic and political variables proposed by Ibn Khaldun by using quantitative approach of Vector Autoregression (VAR) and Granger Causality test.There are some important findings. First, the variable W (welfare) has a significant effect on the level of development of a State (DEV). When a country has a good level of economic growth, then the physical development of a State is relatively good and positive. Vice versa. Second, the N variable (society) has a significant effect on the level of development of a State (DEV). This conclusion is in line with Ibn Khalduns thesis that the quantity and quality of human resources, especially those who work productively, will be able to improve the economy and the development of a State.Another conclusion is that the relatively stable state of the economy, the current government at that time will tend to have the power to survive in its leadership dynasty. In addition, with the good economic conditions and wealth of a State, the position and condition of the people will get better.